The Strategic Role of Human Resources Auditing in Crisis Resilience - Alice ȘTEFĂNESCU; Daria MARIN (Revista de Management Comparat International)
Human resources auditing has emerged as a critical strategic tool for increasing organizational resilience, providing solutions to vulnerabilities and challenges that arise during times of crisis. This article examines the theoretical underpinnings of HR audits, emphasizing their integration with broader frameworks for risk management and strategic planning. By exploring proactive and reactive audit approaches, the study highlights their distinct impacts on organizational adaptability and continuity. Proactive audits are underscored for their role in identifying vulnerabilities and fostering a culture of preparedness, while reactive audits are discussed as essential for immediate damage control. Key challenges such as aligning audits with regulatory requirements and leveraging advanced analytics are also addressed. Finally, the article offers recommendations for implementing HR audits as a foundational mechanism for fostering resilience, ensuring not only crisis mitigation but also long-term organizational growth and sustainability